The crisis of ideology and marginalization of the social consciousness - Golovanov, Borys (Actual Problems of Mind, 2017)
The author considers the crisis of ideology in post-soviet type of society as the formation of the so called «one-day ideology» without sufficient theoretical conceptualization of this phenomenon. By employing an approach from cultural studies he proposes to avoid one-sidedness by understanding the essence of ideology and to consider it as a cultural phenomenon which converts culture to its own instrument.